Identifikasi Perilaku Asertif Peserta Didik di Mts Miftahul Jannah Palangkaraya: Identification Of Assertive Behavior Of Studentsin Miftahul Jannah Palangkaraya MTs - Darmohing Darmohing; Esty Aryani Safithry (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The purpose of this study was to identify assertive behaviour of students at MTs Miftahul Jannah Palangkaraya. The research subjects were eight people, consisting of 3 students, two homeroom teachers, two subject teachers, and 1 BK teacher. The technique of collecting data uses observation and interviews. The research approach used in this study is qualitative. The results of the survey show that: Students at MTs Miftahul Jannah Palangkaraya have not shown assertive behaviour, this is indicated by several aspects of assertive behaviour that have not been able to be demonstrated by students, such as in the demand aspect, students have not been able to hold responsibility and maintain personal rights with well. In the issue of rejection, the students have not been able to reject it well, students do not say Yes or No to the contrary wishes of friends. In the aspect of self-expression, students have been able to express thoughts or ideas, but have not been able to express feelings properly and have not been able to criticise wisely. In the aspect of praise, students have not been able to give and receive approval. In the role aspect of the conversation, students can start the discussion well, but have not been able to finish the conversation well.